What interventions are required to achieve gender balance in political representation at the local government level? - Barungi, Mildred; Nakazi, Florence; Kasirye, Ibrahim (Economic Policy Research Centre, 2021)
Women remain underrepresented in local government politics which offers men an unfair advantage,ultimately overshadowing women in decision-making. It also implies that issues that uniquely affect women may not be prioritised during planning and budgeting. To attain gender parity in political representation at the local government level, Government should design and implement a mentorship program, create a special fund for female political contenders, and launch campaigns to shift the harmful social norms.